Religious Ethical Foundations for AI-Supported Deep Learning in Education: Systematic Literature Review on Teacher Values, Beliefs, and Ethical Teaching Practices - Eva Siti Faridah; Isep Djuanda; Winda Nidya Putri; Eda Laelasari (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: The digital technology era has transformed the way of learning and communicating within Islamic education. In an entirely online environment, the focus extends beyond academic achievement to include character building, spirituality, and higher-order thinking skills. Deep learning has emerged as a meaningful, reflective, and contextual pedagogical strategy. Currently, the integration of Artificial Intelligence (AI) in the education sector has reached a major transformative stage through the application of deep learning. This technology enables highly precise personalized learning, automated assessment, and the development of virtual assistants capable of understanding students' emotional needs. Methodology: This research employs a Systematic Literature Review (SLR) based on the PRISMA 2020 Statement. Results: After going through the 2020 PRISMA guidelines, we started with 37 studies. Out of those, 22 actually fit our inclusion criteria for this Systematic Literature Review. Seven of these studies came from Indonesia. Iraq, the USA, the UK and China each had two. The rest—just one each—came from South Africa, Turkey, Spain, Greece, Russia, Australia, and Central Europe. Applications/Originality/Value: Amidst the rapid advancement of AI technology in Deep Learning processes, the teacher remains a central and irreplaceable figure. AI must be positioned as a tool (wasīlah), not a replacement for educators. Teachers do not merely teach; they serve as ethical mentors who ensure that AI technology remains aligned with faith, spiritual values, and moral standards. The original contribution of this research lies in the formulation of a conceptual framework for integrating religious values into the design and implementation of AI-based learning, ensuring that technology not only enhances cognitive achievements but also shapes the character and spirituality of students.